Antibacterial and antibiofilm effects of essential oil components, EDTA and HLE disinfectant solution on Enterococcus, Pseudomonas and Staphylococcus sp. multiresistant strains isolated along the meat production chain - Caballero Gómez, Natacha; Manetsberger, Julia; Benomar, Nabil; Castillo Gutiérrez, Sonia; Abriouel, Hikmate (Frontiers in Microbiology, 2022)
The spread of multidrug resistant (MDR) bacteria and resistance genes along the food chain and the environment has become a global, but silent pandemic. To face this challenge, it is of outmost importance to develop efficient strategies to reduce potential contamination by these agents. In the present study, 30 strains of Enterococcus sp., Staphylococcus sp. and Pseudomonas sp. isolated from various surfaces throughout the meat production chain in a goat and lamb slaughterhouse were characterized as MDR bacteria harbouring several antibiotic resistance genes (ARGs). The antimicrobial efficacy of natural essential oils (carvacrol “CA”, cinnamaldehyde “CIN”, eugenol “EU”, geraniol “GE”, limonene “LI” and thymol “TH”), HLE disinfectant and EDTA was tested against these MDR bacteria. Results showed that Minimum Inhibitory Concentrations (MIC) were compound and strain dependent. In addition, the synergistic effect of these antimicrobials was evaluated at ½ MIC. Here our study showed particularly promising results regarding the inhibitory effect at sub-inhibitory concentrations, which were confirmed by the analysis of bacterial growth dynamic over 72 h. Furthermore, the inhibitory effect of essential oils, HLE and EDTA or their combinations was studied in developing and established biofilms of MDR bacteria obtaining variable results depending on the morphological structure of the tested strain and the phenolic character of the essential oil. Importantly, the combination of essential oils with HLE or EDTA showed particularly positive results given the effective inhibition of biofilm formation. Moreover, the synergistic combinations of EU and HLE/EDTA, TH, CA, GE, LI or CIN + EDTA/HLE caused log reductions in established biofilms of several strains (1-6 log10 CFU) depending on the species and the combination used, with Pseudomonas sp. strains being the most susceptible. Given these results, we propose novel antimicrobial formulations based on the combination of sub-inhibitory concentrations of essential oils and HLE or EDTA as a highly promising alternative to currently used approaches. This novel strategy notably shows great potential to efficiently decrease the emergence and spread of MDR bacteria and ARGs in the food chain and the environment, thus supporting the decrease of resistomes and pathogenesis in clinical and industrial areas while preserving the antibiotic therapeutic action.